Pengaruh Pandemi Covid-19 dan Karakteristik Perusahaan terhadap Manajemen Laba Akrual - Bahrun Nafis; Nurzi Sebrina (Jurnal Eksplorasi Akuntansi, 2023)
This study aims to analyze the effect of the Covid-19 pandemic and company characteristics on accrual earnings management. Accrual earnings management is the dependent variable in this study as measured by absolute discretionary accruals using the Modified Jones Model by Dechow (1995). The Covid-19 pandemic is an independent variable in this study measured by a dummy variable that takes 1 if the observation period of the pandemic is 2020, and 0 otherwise. Company characteristics are independent variables which in this study are represented by profitability as measured by ROA, leverage as measured by DER, and firm size as measured by the natural logarithm of total assets. The population of this study were companies that were heavily affected by the Covid-19 pandemic, the tourism, restaurant and hotel sectors and the retail sector which were listed on the Indonesia Stock Exchange in 2019-2020 using the sampling method, namely the purposive sampling technique so that the final sample of this study was 57 companies. The analysis technique used is multiple linear analysis techniques. Overall, the results of this study indicate that the Covid-19 pandemic has no effect on accrual earnings management. The characteristics of the company, namely profitability and company size also have no effect on accrual earnings management, and leverage has a positive effect on accrual earnings management.